Co łączy i dzieli nazwy odgłosów zwierząt i ludzi? - Kładoczny, Piotr (Zoophilologica. Polish Journal of Animal Studies, 2020)
The article provides is a comparison of the names of human and animal sounds, which belong to a larger collection of vocabulary that defines the world of auditory perceptions. The historical, grammatic and semantic regularities are identical to them. Differences are noticed in detailed meanings and in the pragmatic of these names, which includes among other things, a much higher incidence of the names of human sounds. Linguistic relativism is more closely covered by the names of animal sounds. The widespread use of animal names for sounds in relation to humans is accompanied by regular negative value and the expression of contempt against the person designated as sound performer.